Neglected Pathways: Examining the Central Government's Oversight of Madrasah Development - Zainuddin Zainuddin; Sulaiman W.; Saifullah Idris; Andriansyah Andriansyah; Jalwis Jalwis (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
This study examines the central government’s neglect of madrasah development in the Special Autonomous Region of Aceh, which may hinder the achievement of inclusive and equitable education. While previous research has largely focused on normative and descriptive aspects, this study addresses the overlooked implications of this neglect. The purpose of this research is to analyze and evaluate the forms, factors, and impacts of the central government’s neglect of madrasah development in Aceh. A descriptive qualitative approach with a case study design is employed to provide a comprehensive analysis of the issue. The findings indicate that government neglect manifests in several ways, including limited routine funding for curriculum development, resulting in inadequate learning materials and compromised educational quality. Furthermore, madrasah infrastructure has not been prioritized, resulting in insufficient facilities that hinder effective teaching. Additionally, low incentives for madrasah educators have negatively affected their welfare and motivation. These findings underscore the need for more equitable educational policies and highlight the urgency of increasing governmental support for madrasah development, particularly in special autonomous regions. The implications of this research emphasize the importance of addressing these systemic issues to promote quality education and improve the overall well-being of educators and students in the region.